A descriptive analysis of the dynamics of labor market outcomes of 4Ps beneficiaries - Aubrey D. Tabuga; Arkin A. Arboneda; Anna Rita P. Vargas (Philippine Institute for Development Studies (PIDS), 2021)
This study aims to understand the nuances and dynamics in the labor market outcomes of 4Ps beneficiaries. The 4Ps or Pantawid Pamilyang Pilipino Program is the Philippine government's key social assistance program with the purpose of breaking inter-generational poverty by incentivizing human capital investment. To help achieve human capital development, accessing sustainable livelihood is crucial. Using the survey data sets collected and used in previously conducted studies on the 4Ps program, this study formed a panel of households and members to examine the changes or the lack of changes in labor status of individuals across the years. The idea is to draw insights that can be utilized in the design or redesign and implementation of related programs such as the Sustainable Livelihood Program for improving the labor market outcomes of 4Ps beneficiaries. The study finds a wide gender gap in terms of labor market status, with males being better off in having a stable work status. Meanwhile, majority of females exclude themselves from the labor force to do unpaid work in the form of household and family duties. The study highlights the importance of the Sustainable Livelihood Program, which was found to mostly benefit women, and the need for sustainable and fully-packaged livelihood programs that target young women and young mothers in poorer communities. For women who engage in economic activities, the study found that they usually remain in the same industry within the period of interest. Meanwhile, male adult members of 4Ps households appear to be more flexible in the way they participate in the labor force. While these results reflect women's lack of flexibility because of their socially dictated roles, these show important aspects for possible interventions for women in 4Ps households.
Keywords: 330; Pantawid Pamilyang Pilipino Program; labor dynamics; labor market outcomes